2015
DOI: 10.1108/jabs-11-2014-0093
|View full text |Cite
|
Sign up to set email alerts
|

Continuous improvement in Vietnam: unique approaches for a unique culture

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…Employee involvement and empowerment are found to have positive impacts on innovation in Vietnamese companies (Dinh et al, 2006;Nguyen and Robinson, 2015). Wallace et al (2016) showed a positive indirect effect from employee involvement to innovation.…”
Section: Organizational Culture and Employee Innovationmentioning
confidence: 99%
“…Employee involvement and empowerment are found to have positive impacts on innovation in Vietnamese companies (Dinh et al, 2006;Nguyen and Robinson, 2015). Wallace et al (2016) showed a positive indirect effect from employee involvement to innovation.…”
Section: Organizational Culture and Employee Innovationmentioning
confidence: 99%
“…After that, numerous studies have defined and measured quality management practices, and analyzed their implementation in enterprises in both developed countries, such as Japan [22], the US [23][24][25], Hong Kong [14], Australia [26,27], Spain [28][29][30], and Singapore [31]; and developing countries, such as China [14,24,32], South Korea and Taiwan [33], Malaysia [34], Turkey [35,36], Thailand [37], Mexico [25], Ghana [38], Tunisia [39], and Vietnam [6,40,41].…”
mentioning
confidence: 99%
“…Some studies showed that different approaches to CI are equally effective in driving improvements in both technical and social systems, even though there are significant differences in the project size, type, location, and industrial sector (Jin & Doolen, 2014). Another study found out that the success of the use of CI approaches depends on the culture of the organisation and the capability of the managers and leaders to implement those approaches effectively (Robinson & Phuong, 2015). Robinson and Phuong (2015) suggested that every unique culture of the organisation should follow unique approaches of CI to ensure improvement in quality.…”
Section: Conventional Approaches To Continuous Quality Improvementmentioning
confidence: 99%
“…Another study found out that the success of the use of CI approaches depends on the culture of the organisation and the capability of the managers and leaders to implement those approaches effectively (Robinson & Phuong, 2015). Robinson and Phuong (2015) suggested that every unique culture of the organisation should follow unique approaches of CI to ensure improvement in quality. Wahid and Ismail (2017) conducted a study to identify the antecedents for relationship quality model that would help the organisations to increase the quality of their services.…”
Section: Conventional Approaches To Continuous Quality Improvementmentioning
confidence: 99%